Critical gaps in understanding treatment outcomes in adolescents and young adults with lymphoma: A review of current data - Priyanka A. Pophali; Lindsay M. Morton; Susan K. Parsons; David Hodgson; Gita Thanarajasingam; Carrie Thompson; Thomas M. Habermann; Kerry J. Savage (eJHaem, 2023)
Abstract Adolescents and young adults (AYA) with lymphoma experience treatment‐related effects in the short and long term that impact their quality of life and survivorship experience. The effort to improve outcomes for AYA lymphoma survivors requires understanding the available literature, identifying current knowledge deficits, designing better clinical trials incorporating the patient perspective, using novel tools to bridge data gaps and building survivorship guidelines that translate research to clinical practice. This review article summarizes the current state of lymphoma treatment‐related outcomes in AYAs and provides future direction.